School readiness of maltreated children: Timing, type, and chronicity of maltreatment - Bell, Megan; Bayliss, Donna; Glauert, Rebecca; Ohan, Jeneva (International Journal of Population Data Science, 2018)
Introduction Children who have been maltreated during early childhood may experience a difficult transition into schooling, due to maladaptive development of the abilities that are important for positive school adaptation. An understanding of how different dimensions of maltreatment relate to children’s school readiness is important for informing appropriate supports for maltreated Objectives and Approach In this study, the Australian Early Development Census scores of 19,203 children were linked to information on child maltreatment allegations (substantiated and unsubstantiated), including the type of alleged maltreatment, the timing of the allegation (infancy-toddlerhood or preschool), and the total number of allegations (chronicity). Results Children with a maltreatment allegation had increased odds of poor school readiness in cognitive and non-cognitive domains. Substantiated maltreatment was associated with poor social and emotional development in children, regardless of maltreatment type, timing, or chronicity. For children with unsubstantiated maltreatment allegations, developmental outcomes according to the type of alleged maltreatment were more heterogeneous; however, these children were also at risk of poor school readiness irrespective of the timing and/or chronicity of the alleged maltreatment. Conclusion/Implications The findings suggest that all children with maltreatment allegations are at risk for poor school readiness; these children may benefit from additional support to increase the chance of a successful school transition. Interventions should commence prior to the start of school to mitigate early developmental difficulties.